Coffee leaf rust and berry borer management in agroforestry systems: A systematic literature review - Yakdiel Rodriguez-Gallo; Hector Cañas; Jordi Cruz; Manuel Cardona; Guillermo Medina-González (Smart Agricultural Technology)
This study presents a Systematic Literature Review (SLR) on the management of Coffee Berry Borer (CBB) and Coffee Leaf Rust (CLR) in Coffee Agroforestry Systems (CAFS). Despite extensive research on pest and disease management in CAFS, there is a notable absence of literature reviews or bibliometric analyses regarding the study of the CBB and CLR. The novelty of this work lies in offering a comprehensive synthesis of recent research and identifying the technologies employed in these studies, providing valuable insights for future developments in the field. Using the PRISMA protocol and Bibliometrix tool, the research analyzed 51 relevant studies from Web of Science and Scopus databases, covering the period from 2002 to August 2024. The analysis revealed an increasing trend in publications on CBB and CLR in CAFS in recent years. Traditional techniques, such as visual plant observation, pheromone traps, and spore sedimentation traps, remain prevalent. However, the use of advanced technologies in CAFS is still limited. Findings highlight the significant impact of shade on pest dynamics, the importance of biodiversity in pest control, and the need for integrated pest management strategies. The study concludes that while traditional techniques play a crucial role in pest and disease monitoring in CAFS, there is significant untapped potential in integrating advanced technologies such as sensors, UAVs, IoT, robotics, and AI. The limited use of these technologies in CAFS underscores the need for future research to drive their adoption and optimization, aiming to improve sustainable pest and disease management in these complex systems.